Theoretical and practical aspects of biotechnology meat with micro-particle whey protein - Olga Nikolaevna Nazarova; Valentin Ivanovich Shipulin (Наука. Инновации. Технологии)
The article describes the milk protein concentrates used in the meat industry. The results of studies of functional and technological properties of whey proteins. Studied model systems with minced micro-particle whey protein.